Assessment of the safety of the feed additives acetic acid, calcium acetate and sodium diacetate for fish (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2023)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety of acetic acid, calcium acetate and sodium diacetate as technological feed additives (preservatives) for salmonids/fish. The additives are already authorised for use for all animal species other than fish. In previous opinions, the FEEDAP Panel concluded that a maximum concentration of 2,500 mg acetic acid/kg complete feed (or 1,000 mg/L water for drinking) was safe for poultry, pigs and pet animals. Ruminants were considered to exhibit a higher tolerance. Due to lack of data for salmonids, the Panel could not conclude on the safety of acetic acid and its salts for fish. The applicant has provided supplementary information consisting in a tolerance study in Atlantic salmon (Salmo salar) and a literature search to support the safety of acetic acid in fish. Considering all the available information, the FEEDAP Panel concluded that acetic acid (and its salts by analogy) is considered safe for fish up to the maximum recommended supplementation level of 2,500 mg acetic acid/kg complete feed.